Trends of admission and deaths of burn patients (2000 to 2016) in a tertiary care hospital of Maharashtra: a time series analysis - Kishanrao, Domple Vijay; Wadde, Satish Kishanrao (International Journal Of Community Medicine And Public Health, 2019)
Background: The World Health Organization projects that by 2020, injuries will surpass infectious diseases as the leading cause of death worldwide. Therefore we conducted the present study with objective to identify trends of admissions and deaths of burn patients and to forecast the number of cases of admission and deaths in a tertiary care hospital, Maharashtra by using time series analysis. Methods: The present retrospective study was conducted at a tertiary care hospital of Maharashtra in the month of September 2017. Month wise admissions (7674 patients) and deaths (2865) of burn patients in last seventeen years (2000 to 2016) were used for this purpose. Data was analyzed by using SPSS version 16. Results: There was increasing trend of admissions of burn patients in December to January. Increase in the deaths was also observed in the months of February and March by simple seasonal model of Expert Modeler in SPPS. This predicted 30-44 admissions and 9-13 deaths of burn patients in the year of 2019. Conclusions: The trends and forecasting of admissions and deaths of burn patients will be useful for hospital administrators for management of cases.